APPLICATION OF DISTANT PRE-CONDITIONING TECHNIQUE IN PATIENTS WITH SEVERE TRAUMATIC BRAIN INJURY - L. L. Plotkin; Yu. P. Klink (Вестник анестезиологии и реаниматологии)
The abstract describes the prospective randomized study which included 60 patients with severe traumatic brain injuries divided into two groups. In the group under the study (n = 30) the distant ischemic preconditioning has been applied which is commonly used for planned surgeries and it allowed achieving statically signiﬁcant decrease in the time of coming out from coma, the duration of stay in the intensive care ward and increase the rate of 28 day survival.